Construction of flame-retardant and water-resistant polybutylene terephthalate composites by reactive extrusion - Ran, Guowen; Zhang, Jingfan; Yuan, Yihui; Xie, Haisheng; Li, Tao; Lan, Xiucai; Cao, Yanxiao (Frontiers in Materials, 2025)
The combination of aluminum diethylphosphinate (ADP) and melamine pyrophosphate (MPP) has been extensively utilized in flame-retardant polybutylene terephthalate (PBT) composites. However, the hydrophilic nature of ADP and MPP leads to their migration to the surface or separation from the PBT matrix under the influence of heat and moisture, which subsequently results in the degradation of both flame retardancy and mechanical properties. In this study, reactive epoxy groups were introduced onto the surface of the flame retardant (FR) using a simple method. The resulting encapsulated flame retardant (EP@FR) was then incorporated into PBT via a twin-screw extruder. During extrusion process, the reactive epoxy groups interacted with the free terminal hydroxy and carboxy derived from the PBT, forming covalent bonds at the interface of FR and PBT, thereby enhancing flame retardancy and water resistance. With the addition of 16.0 wt% EP@FR, the PBT/EP@FR composites achieved a UL-94 V-0 rating with an LOI value of 28.5%. Notably, the mechanical properties and UL-94 V-0 rating of the PBT/EP@FR composites were maintained even after immersion in water at 70°C for 14 days. It is expected that this work can provide a promising strategy for the development of flame-retardant and water-resistant PBT composites.